2008
DOI: 10.1074/jbc.m708164200
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Phycobiliproteins

Abstract: Phycobilin lyases covalently attach phycobilin chromophores to apo-phycobiliproteins (PBPs). Genome analyses of the unicellular, marine cyanobacterium Synechococcus sp. PCC 7002 identified three genes, denoted cpcS-I, cpcU, and cpcV, that were possible candidates to encode phycocyanobilin (PCB) lyases. Single and double mutant strains for cpcS-I and cpcU exhibited slower growth rates, reduced PBP levels, and impaired assembly of phycobilisomes, but a cpcV mutant had no discernable phenotype. A cpcS-I cpcU cpcT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 45 publications
5
47
0
Order By: Relevance
“…Phylogenetic analyses of cyanobacteria based on their PCB lyases suggested that the heterodimeric lyases CpcS-1 and CpcU are also responsible for PCB attachment in Synechocystis sp. PCC 6803 (Shen et al 2008). These findings complement our knowledge of the biosynthesis pathway of the APC trimer.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…Phylogenetic analyses of cyanobacteria based on their PCB lyases suggested that the heterodimeric lyases CpcS-1 and CpcU are also responsible for PCB attachment in Synechocystis sp. PCC 6803 (Shen et al 2008). These findings complement our knowledge of the biosynthesis pathway of the APC trimer.…”
Section: Introductionsupporting
confidence: 69%
“…Tryptic digestion was performed as described with modifications (Arciero et al 1988;Shen et al 2008). Briefly, rAPCs in 50 mM potassium phosphate (pH 7.0) were acidified with 1 N HCl to pH 2.0.…”
Section: Tryptic Digestion Of Apcmentioning
confidence: 99%
See 2 more Smart Citations
“…The lyase is ubiquitous among cyanobacteria and has been subdivided into several classes (9). Some classes including the enzyme from Synechococcus sp.…”
Section: Discussionmentioning
confidence: 99%